2011
DOI: 10.1167/iovs.11-7789
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Confocal Investigation on Salzmann Nodular Degeneration of the Cornea

Abstract: This work illustrates the confocal microscopic findings associated with LM and TEM observations in patients with advanced SND. Our data revealed milder changes of the epithelium together with more pronounced changes of the basement membrane and Bowman's layer, which are aspects of increased keratocyte activity and an altered nerve pattern. All of these structures seem to contribute to the characteristic corneal disorganization of SND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
0
16
0
8
Order By: Relevance
“…23 They attributed these changes to dry eye and subbasal nerve loss. More recently, Roszkowska et al 32 showed severe superficial epithelial changes by IVCM in Salzmann nodular degeneration of the cornea by IVCM. They observed enlarged squamous cells with prominent nuclei and bright margins in the superficial layer of the central corneal epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…23 They attributed these changes to dry eye and subbasal nerve loss. More recently, Roszkowska et al 32 showed severe superficial epithelial changes by IVCM in Salzmann nodular degeneration of the cornea by IVCM. They observed enlarged squamous cells with prominent nuclei and bright margins in the superficial layer of the central corneal epithelium.…”
Section: Discussionmentioning
confidence: 98%
“…228 Likewise, analysis by IVCM of cases with Terrien’s marginal corneal degeneration have found a decrease in the subbasal nerve density and branching. 229 …”
Section: Correlation Of Corneal Nerve Alterations To Corneal Sensmentioning
confidence: 98%
“…The nerve fibre appears as an undulating sloping line with high intensity. Moreover, there is a presence of reflective cellular elements near these fibres 27 28. SSCM (Confoscan 2) was used to capture the images of Salzmann's nodular degeneration.…”
Section: Corneal Layers In Diseasementioning
confidence: 99%